DESAIN MODEL KANVAS PADA PENGEMBANGAN BISNIS PRODUK INOVASI UNTUK MEMENANGKAN SEGMEN PASAR MILENIAL (STUDI PADA PT. TELEKOMUNIKASI INDONESIA, Tbk) - Almira, Winona; Handriana, Tanti (Universitas Muhammadiyah Surakarta, 2019)
Millennial is currently the most important target in the marketing world in the digital age. Based on the survey, the number of internet service users in Indonesia is dominated by the millennial segment. However, millennials have different characteristics. Thus, special strategies are needed to penetrate and win planned markets. In this study, a qualitative analysis was used by implementing the concept of business model canvas in order to obtain a comprehensive business plan for the digital and telecommunication company. The canvas designs resulted in this study not only can be applied in the digital and telecommunications companies, but also in all fields of companies that start to utilize digital applications in their services.